National history in Southern Africa: Reflections on the 'Remember Cassinga?' exhibition - Williams, Christian A. (Kronos: Southern African Histories, 2017)
'Remember Cassinga?' is the name of an exhibition of photographs and histories prepared for display at the University of the Western Cape in South Africa and the National Archives of Namibia in April and May 2010. The exhibition examines the SWAPO camp at Cassinga, Angola, where more than six hundred Namibians were killed on 4 May 1978 during a South African attack. In contrast to the competing national histories, which have condemned or justified the attack by labelling Cassinga a 'refugee' or a 'military' camp, the exhibition renders Cassinga before the attack, arguing that the terms 'refugee' and 'military' obscure the community which formed at this site. At the same time, the exhibition examines how photographs have been used to support Cassinga's two national narratives and how people have become victims of this form of historical production.